Design of low power bandgap voltage reference - Wang, Daichao (2016)
Voltage reference is a very basic and important part of integrated circuit design. It is being used to provide an accurate and stable reference voltage for different circuits This project is designed base on the CSM0.18µM process. A transistor level band-gap voltage reference is being presented. The voltage reference is designed using the current mode approach. The voltage reference work with 1.2V supply voltage and produce a typical 998.5mV reference voltage. The temperature coefficient of this design is 33.66ppm/°C from-20°C to 80°C. The circuit is very stable with a phase margin of 85.7° and gain margin of 36.67dB. The power supply rejection ration of the design is around -22 at 100 Hz.